Dynamic Methods and Process Advancements in Mechanical, Manufacturing, and Materials Engineering
DOI: 10.4018/978-1-4666-1867-1.ch012
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Study of Chip Formation Process in Orthogonal Machining

Abstract: This paper examines the plane strain 2D Finite Element (FE) modeling of segmented, as well as continuous chip formation while machining AISI 4340 with a negative rake carbide tool. The main objective is to simulate both the continuous and segmented chips from the same FE model based on FE code ABAQUS/Explicit. Both the adiabatic and coupled temperature displacement analysis has been performed to simulate the right kind of chip formation. It is observed that adiabatic hypothesis plays a critical role in the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Therefore, steady simulation process cannot predict tool wear matches the experiments. Table 13 showed that the error percentages between simulated wear and experiments were (4.6%‐10%), which is accepted compared to recent researches such as Eliaz et al, 2020 13 who could achieve 12.5% minimum tool wear error percentage.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, steady simulation process cannot predict tool wear matches the experiments. Table 13 showed that the error percentages between simulated wear and experiments were (4.6%‐10%), which is accepted compared to recent researches such as Eliaz et al, 2020 13 who could achieve 12.5% minimum tool wear error percentage.…”
Section: Discussionsupporting
confidence: 52%
“…Priyadarshini et al 13 have mentioned that there are three FEM approaches for defining the motion of material points through the mesh grid during simulation running time. These approaches are LAG, EUL, and ALE approach.…”
Section: Introductionmentioning
confidence: 99%
“…The cutting speed has been maintained constant and only the rpm is varying in the experiments. Due to the constant cutting speed and only varying rpm, for ease of analysis the workpiece is considered to be rectangular and the rpm is converted to linear speed to machine the rectan-gular surface, which has been referred from existing literature [12]. Care has been taken to scale in proportion, not to affect the results and the speed of simulations.…”
Section: Details Of the Geometrymentioning
confidence: 99%
“…The constants in the equation 1 represent: A = Yield stress corresponding to a 0.2 offset point. ference rule and mechanical response by explicit central-difference rule [6,12,23].…”
Section: Johnson-cook Plasticity Modelmentioning
confidence: 99%
See 1 more Smart Citation